2021
DOI: 10.1097/inf.0000000000003349
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Methicillin-susceptible Versus Methicillin-resistant Staphylococcus aureus Infections in Pediatrics

Abstract: Background: The epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) has changed in recent years. The present article is intended to establish differences between clinical, laboratory and imaging findings and outcomes of MSSA and MRSA infections, as well as among subgroups of infection such as skin and soft tissue infection, osteoarticular, bacteremia or pneumonia in a pediatric populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
8
1
1
Order By: Relevance
“…In our study, nearly 43% of S. aureus isolates from the lesional skin samples of AD pediatric patients were MRSA. This is consistent with previous studies that reported 10%–42% MRSA isolates among S. aureus ‐positive AD skin cultures 8,35,36 . In AD skin cultures, MRSA strains are on the rise and are more virulent than MSSA 37–39 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, nearly 43% of S. aureus isolates from the lesional skin samples of AD pediatric patients were MRSA. This is consistent with previous studies that reported 10%–42% MRSA isolates among S. aureus ‐positive AD skin cultures 8,35,36 . In AD skin cultures, MRSA strains are on the rise and are more virulent than MSSA 37–39 .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies that reported 10%-42% MRSA isolates among S. aureus-positive AD skin cultures. 8,35,36 In AD skin cultures, F I G U R E 6 Expression of ELOVL3 and ELOVL4 in human primary keratinocytes stimulated with MRSA and neutralizing antibodies. HEKs were differentiated and preincubated with isotype control antibodies or neutralizing antibodies against TNFα (0.1 μg/ml), IL-1β (10 ng/ ml), IL-36γ (1.0 μg/ml), IL-6 (0.1 μg/ml), and IL-33 (1.0 μg/ml) separately or in combination (all same concentrations) for MRSA strains are on the rise and are more virulent than MSSA.…”
Section: Discussionmentioning
confidence: 99%
“…and S. aureus and another with S. aureus and Streptococcus pyogenes ). The prevalence of methicillin-resistant S. aureus was 52.3%, slightly higher than that reported in other studies in Colombia ( 14 , 15 ). The correlation between the phenotypic profile and the detection of the mecA gene was 100%.…”
Section: Discussioncontrasting
confidence: 63%
“…Additionally, one of the MRSA strains was resistant to macrolides, specifically to erythromycin ( Table 2 ). The MRSA strains included in this study showed resistance profiles similar to those of clinical isolates circulating in hospital settings in Colombia [ 30 , 31 ]. S. aureus , including MRSA strains, has been reported to be one of the leading causes of nosocomial infections worldwide, especially among patients in surgery, undergoing hemodialysis, and in ICU units, because of the long-term use of venous and urinary catheters [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%